Not in my homeland: Immigrant CEOs and the geography of corporate social irresponsibility - Bu, Juan; Wang, Stephanie Lu; Lee, Yejee; Li, Dan (Strategic Management Journal, 2025)
Research Summary This study examines how immigrant CEOs influence the geography of multinational enterprises' (MNEs) corporate social irresponsibility (CSI) incidents. Building on place attachment theory and social capital theory, we theorize that immigrant CEOs have strong psychological attachment to and social capital in their homeland countries, which could reduce the occurrence and media disclosure of their MNEs' CSI incidents in those countries. Moreover, this effect will be further enhanced if the CEO emigrates as an adult, if the focal firm has a higher sustainability rating, and if the CEO's homeland country has lower press freedom. A difference‐in‐differences analysis using a propensity score‐matched sample of MNEs from the US S&P 500 during the 2007–2020 period supports our arguments. Managerial Summary Why do firms engage in different levels of corporate irresponsibility in different locations? Our study reveals a connection between the appointment of an immigrant CEO and the locations of multinational enterprises (MNEs') irresponsible incidents. Immigrant CEOs can not only reduce their MNEs' harmful acts in their homelands because of their strong psychological attachment but also leverage social relationships in their homelands to mitigate media coverage of their firms' negative incidents there. Such impacts of appointing immigrant CEOs are subject to CEOs' immigration as adults or children, their firms' sustainability ratings, and their homeland countries' press freedom.